(untitled) - Fitzsimmons, James A. (Boston, 2008)
Balancing conceptual and applied coverage of all aspects of the management and operation of services, "Service Management" has maintained the position as market leader through five previous editions. It is the most comprehensive and widely used introduction to service operations on the market, written by one of the top authorities on the subject, and it is designed to develop students' skills in both strategic and operational issues pertaining to services.New material on Professional Service Firms highlights IBM's initiative to establish a Service Science, Management, and Engineering discipline.
Keywords: Service industries,Công nghiệp dịch vụ; Management,Quản trị